The narrative structure in Ibrahim Nasrallah’s novel the second war of the dog. An analytical study - Abouelnour, Moustafa Mohamed; Alsharef, Ali Kamel Ali; Adel, Mohammed Ahmed Abou; Alhourani, Mohammad Issa (Edelweiss Applied Science and Technology, 2024)
This research explores the narrative structure in the novel The Second War of the Dog (2016) by Palestinian writer Ibrahim Nasrallah from a postmodern perspective. The study aims to analyze various narrative elements in the novel, such as time, setting, characters, and plot, and to examine how the author employs postmodern techniques to construct his fictional world. Additionally, the research seeks to uncover the intellectual and aesthetic meanings embedded in this narrative structure and its connection to contemporary cultural and social contexts. The significance of the novel lies in its portrayal of societal transformations and realities through a fantastical and satirical lens, exposing the flaws and distortions in society. The novel is set in a dystopian, corrupt city symbolized by the main character, Rashid, who oscillates between two opposing realms: the world of good and the world of evil. The study employs a descriptive-analytical approach, utilizing literary criticism tools and postmodern theories to analyze the novel’s text.